Re-orienting narratives of moral injury towards positive development: The experiences of emerging adults with child welfare histories. (June 2023) - Soffer-Elnekave, Ruth; Haight, Wendy; Nashandi, Ndilimeke J.C.; Cho, Minhae; Suleiman, Johara; Park, Sookyoung
Highlights: Participants reporting moral injury described a re-orientation of their narratives through meaning making. Hope, gratitude, forgiveness and courage were themes in the re-orientation of morally injurious narratives. Supportive relationships, engagement with spiritual beliefs and practices, and prosocial engagement supported narrative re-orientation. Participants' advice highlighted the need to enhance foster youths' relationships with professionals and care providers. Abstract: This paper is the second in a series of papers from a mixed methods study examining moral injury in childhood and adolescence as described by emerging adults with histories of child welfare involvement. This paper focuses on the ways emerging adults may alleviate their moral injury, grow and develop. Twenty -eight emerging adults (18–26 years) who reported exposure to morally injurious events during childhood or adolescence on a modified version of the Moral Injury Events Scale (MIES; Nash et al., 2013 ) participated in life story interviews. Life story analyses of psychosocial contexts considered resiliency, especially any re-orientation of participants' narratives of moral injury away from the anomie, guilt, shame, and rage characteristic of moral injury, and towards themes such as hope, forgiveness, and gratitude. In addition, psychosocial-spiritual contexts that may support these shifts in meaning were explored through thematic analyses. Findings indicate that supportive relationships, especially with caring adults, engagement with spirituality, and access to prosocial activities provide foster youth with opportunities to re-orient their moral injury narratives, and provide a foundation on which to build towards recovery. Implications for policy, practice and research are discussed.